Personality profile of the institutionalized children of Reception and Action Center, Manila - Dario, Arnaldo L. (Animo Repository, 1994)
This study is to do a personality profile of the institutionalized children of Reception and Action Center, Arroceros, Manila. The protocol are of ages 12 to 18 years of age.The Panukat ng Ugali at Pagkatao (Enriquez and Guanzon, 1993), was the Filipino psychometrical test used to measure specific personality traits, namely: 1) ambisyon, 2) katipiran, 3) katiyagaan, 4) hirap kausapin, 5) lakas ng loob, 6) pagkamaalalahanin, 7) pagkamagalang, 8) pagkamahiyain, 9) pagkamalikhain, 10) pagkamapagbigay, 11) pagkamapagkumbaba, 12) pagkamapagtimpi, 13) pagkamapunahin, 14) pagkamaramdamin, 15) pagkamatulungin, 16) pagkamausisa, 17) pagkapalaaway, 18) pagkapikon, 19) pagkaresponsable, 20) pagkasalawahan, 21) pagkasigurista, 22) pagkasunud-sunuran, 23) sumpong, and 24) tigas ng ulo. The PUP uses the Likert type scale with 1= Hinding-hindi (HH), 2= Hindi (H), 3= ? , 4= Totoo (T), and 5= Totoong-totoo (TT). The scores for each item may range from 1 to 5. A high score on a personality trait means that trait is most likely observed by the respondent. A low mean score on a personality trait means that trait is less observed by the respondent.The internal validity of the test is based on the results of the two validity subscales on the PUP, which are Pagkakaila and/or Kaugalian . Scores of 4 or 5 on four or more items on the Pagkakaila subscale suggests that the scores on the whole test cannot be reliable. If there are scores of 1 or 2 on four or more items on the Kaugalian subscale, this means that the respondent does not possess nor observe the Filipino personality traits measured in the PUP.Among the 45 respondents, two respondents' test results were found to be invalid based on the Kaugalian validity subscale, and 9 tests were found to be invalid based on the Pagkakaila validity subscale.From the 34 valid tests, the Kaugalian subscale had the highest group mean of 4.02. Therefore, most of the respondents, if not all, are culturally Filipino influenced. The Pagkakaila validity subscale showed a group mean of 2.54, the second to the lowest of the personality traits. This means that denying the truth or lying is one of the traits least observed by the respondents.Test scores on the 24 subscales on the PUP shows that the respondents are still considered to be on the average compared with the norms of the PUP.Therefore, the findings from the test results of the PUP shows that the institutionalized children at the Reception and Action Center, Manila, are socially and personally adjusted.